Level of Awareness, Preparedness and Readiness of the Technical - Vocational Education Institutions in the Implementation of the K to 12 Curriculum in Zamboanga Peninsula - Kong, Jocelyn I. (JPAIR Institutional Research, 2017)
The K-12 curriculum is the main focus of the educational system of the Philippines today. Technical-Vocational Education Institutions are mandated to offer the Technical-Vocational Livelihood Track of the K-12 curriculum. The study determined the level of awareness, preparedness and readiness of the Technical-Vocational Education Institutions (TVEI) in the implementation of the K-12 curriculum in Zamboanga Peninsula. The sample consisted of three hundred eight (308) faculty and staff of the selected TVEI in Zamboanga Peninsula for the School year 2014-2015. Both quantitative and qualitative research design using descriptive survey method and total enumeration sampling in the selection of the respondents was employed. A  Likert-Type questionnaire was used in the gathering of data. The findings showed that there was a significant relationship in the level of awareness, preparedness and readiness of the TVEI in the implementation of K-12 curriculum in terms of curriculum, faculty, equipment, facility, funding and infrastructure. However, there are still possible problems that the TVEI had identified in the implementation of the grades 11 and 12 as perceived by the respondents. These are lack of facilities and equipment, insufficient teachers' manual, poverty among students and lack of books. The study recommends that TVEI in Zamboanga Peninsula, partners with CHED, DepEd, TESDA and other agencies to offer or implement the K-12 curriculum in their institution starting school year 2016. TESDA motivates the different TechVoc institutions in terms of fundings and whichever support in assessing the curricular offerings offered by the institution.
Keywords: Technical Vocational Education Institution (TVEI); K-12 Curriculum; descriptive design; Philippines